Preparation and characterization of EVA-sisal fibre composites - Malunka, Mamookho Elizabeth (University of the Free State, 2005)
The main focus of this research project was on sisal fibre as organic filler and the effect of its content on the thermal and mechanical properties of EVA. Sisal is a promising reinforcement for use in composites on account of its low cost, low density, high specific strength and modulus, no health risk, easy availability in some countries and renewability. Ethylene vinyl acetate (EVA) copolymer has a broad range of industrial applications. Uncross-linked and cross-linked EVA and EVA-sisal composites were prepared and characterized. In this work we present and discuss the preparation and characterization of EVA-sisal fibre composites. All the results strongly point to grafting between EVA and sisal, even for samples prepared in the absence of DCP. Gel content results indicate increased cross-linking/grafting with increasing DCP and sisal contents. Grafting between EVA and sisal fibre is confirmed by the porosity and FTIR results. The SEM photomicrographs also support strong fibre-matrix adhesion in the EVA-sisal composites. Grafting, and to a lesser extent cross-linking of EVA, had an impact on the thermal and tensile properties of the composites, because cross-linking and grafting substantially influence the structure and morphology of the composites. The incorporation of sisal in the EVA matrix increases the composites' stiffness. The influence of DCP on the stiffness, however, depends on the amount of sisal in the composite. Elongation at break increases in the presence of DCP, but drastically decreases in the presence of sisal. For pure EVA, stress at break decreases with increasing DCP content, probably because of degradation. It also decreases when 10 % sisal is present in the EVA matrix, but increases for higher sisal contents. In the presence of sisal, increasing DCP content also increases stress at break. Cross-linking and grafting also had an impact on the surface free energy of the samples.
Dissertation (M.Sc. (Chemistry))--University of the Free State, 2005
Keywords: Sisal (Fiber); Fillers (Materials); Polymer blends; Copolymers